The Identification and Characterization of a Novel Alginate Lyase from Mesonia hitae R32 Exhibiting High Thermal Stability and Potent Antioxidant Oligosaccharide Production - Yongshang Ye; Zhiyu Li; Ying Zhou; Xiujun Gao; Dingfan Yan (Marine Drugs)
Alginate lyases are of great importance in biotechnological and industrial processes, yet research on these enzymes from Mesonia genus bacteria is still limited. In this study, a novel PL6 family alginate lyase, MhAly6, was cloned and characterized from the deep-sea bacterium Mesonia hitae R32. The enzyme, composed of 797 amino acids, contains both PL6 and GH28 catalytic domains. A phylogenetic analysis revealed its classification into subfamily 1 of the PL6 family. MhAly6 showed optimal activity at 45 °C and pH 9.0, retaining over 50% activity after 210 min of incubation at 40 °C, highlighting its remarkable thermal stability. The enzyme exhibited degradation activity toward sodium alginate, Poly M, and Poly G, with the highest affinity for its natural substrate, sodium alginate, producing alginate oligosaccharides (AOSs) with degrees of polymerization (DP) ranging from 2 to 7. Molecular docking identified conserved catalytic sites (Lys241/Arg262) and Ca2+ binding sites (Asn202/Glu234/Glu236), while the linker and GH28 domain played an auxiliary role in substrate binding. Antioxidant assays revealed that the MhAly6-derived AOSs showed potent radical-scavenging activity, achieving 80.64% and 95.39% inhibition rates against DPPH and ABTS radicals, respectively. This work not only expands our understanding of alginate lyases from the Mesonia genus but also highlights their biotechnological potential for producing functional AOSs with antioxidant properties, opening new avenues for their applications in food and pharmaceuticals.